2022
DOI: 10.1002/brb3.2589
|View full text |Cite
|
Sign up to set email alerts
|

The burden of epilepsy and unmet need in people with focal seizures

Abstract: Background: Epilepsy is one of the most common neurological conditions worldwide.As a chronic condition, epilepsy imposes a significant burden on people with epilepsy and society. We aimed to assess the burden and unmet need of individuals with epilepsy and their caregivers, focusing on focal seizures, the main type of seizure in adults and children. Methods:A targeted evidence review of the burden of epilepsy, focusing on focal seizures, was conducted to identify articles reporting: epidemiology, mortality, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 138 publications
0
22
1
3
Order By: Relevance
“…Patients with DRE may experience increased comorbidities, an increased risk of injuries, adverse events (AEs) from treatment and premature death. In addition, DRE may impact patients' employment status and quality of life 5,6 . While epilepsy is associated with a considerable economic burden, a country‐based study has suggested how modest improvements in seizure control could provide substantial economic benefits to society, 7 emphasizing the need for new ASMs that provide improved seizure control.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with DRE may experience increased comorbidities, an increased risk of injuries, adverse events (AEs) from treatment and premature death. In addition, DRE may impact patients' employment status and quality of life 5,6 . While epilepsy is associated with a considerable economic burden, a country‐based study has suggested how modest improvements in seizure control could provide substantial economic benefits to society, 7 emphasizing the need for new ASMs that provide improved seizure control.…”
Section: Introductionmentioning
confidence: 99%
“…18,19,21,40 We hypothesize that brain morphology, as assessed using various neuroimaging techniques, may mediate the relationship between ADI and cognition in patients with epilepsy and have additional research underway to test this hypothesis. It should also be noted that epilepsy can place a significant burden on the patient and their support structure (e.g., medical expenses, adverse treatment events, employment concerns, and inability to drive), 41 potentially pushing them into areas with greater neighborhood deprivation. Furthermore, there is evidence to suggest that racialized inequalities in epilepsy result in greater burden among some racial/ethnic groups compared with non-Hispanic White individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy currently affects 1.2% of the population, with ranging symptoms and quality of life (QOL) impairments, defined as an individual's perception of their well-being, such as not being able to drive, strobe light sensitivity, social stigma, or in some cases, needing a full-time caregiver. 1 There are multiple standards of care for treating epilepsy. While the primary approach involves prescribing medication, 30%-40% of people with epilepsy (PWE) are drug-resistant and must find alternative ways to cope.…”
Section: Introductionmentioning
confidence: 99%